Pendidikan Islam dan Upaya Menangkal Hoax di Seputar Pandemi Covid-19 - Sophia, Alma Vita (Fakultas Tarbiyah dan Keguruan, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis, Jawa Barat, Indonesia, 2021)
Education has the main control in a person's mindset. Likewise, Islamic education that is oriented to the Qur'an and Sunnah is very important in controlling one's mindset. Where when people who are educated and religious will have a different fikroh with someone who is uneducated and not religious. In this critical situation of the Covid-19 Pandemic, of course, we receive a lot of news, both from television and from social media, which are indeed very minimal filters, thus requiring us as a society to be smarter in filtering the news we receive. With this Islamic education, of course, it really helps us in warding off hoaxes about the Covid-19 pandemic. Because by using the knowledge of Islamic education that we get, practicing what the Qur'an and Assunnah commands when facing an epidemic, and when receiving news, will make all people from students to us as teachers be wiser in receiving positive news. and negative about Covid-19.